Conscientious objection in health care: the Mexican frame - Álvarez-Díaz, Jorge (2007)
In order to establish the general characteristics of the theoretical problems regarding to the conscientious objection in health care, as well as its possible application within the Mexican framework, this paper makes some basic philosophical considerations to understand what is (and what is not) the conscientious objection, which characteristics must have to consider it like so, and what other figures can take part in the complex world of health care. We end talking about the Mexican frame and the case of voluntary interruption of pregnancy as an exemplification.